2017
DOI: 10.4049/jimmunol.1601711
|View full text |Cite
|
Sign up to set email alerts
|

Fate Decision Between Group 3 Innate Lymphoid and Conventional NK Cell Lineages by Notch Signaling in Human Circulating Hematopoietic Progenitors

Abstract: The role of Notch signaling in human innate lymphoid cell (ILC) differentiation is unclear, although IL-7 and IL-15 promote differentiation of natural cytotoxicity receptor (NCR) NKp44+ group 3 ILCs (NCR+ILC3s) and conventional NK (cNK) cells from CD34+ hematopoietic progenitor cells (HPCs) ex vivo. In this study, we analyzed the functions of Notch in the differentiation of NCR+ILC3s and cNK cells from human HPC subpopulations circulating in peripheral blood by limiting dilution and clonal assays using high-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…In contrast, in vitro culture of identical progenitors in IL-7 + IL-15 and Notch-ligand resulted in the proliferation of both CD7 + and CD7 − progenitors, arguing against IL-15 purely inducing CD7 on responsive progenitors ( Figure 1 A). Consistent with a recent report [ 17 ], Notch signalling and IL-7 appear to impair commitment towards the NK cell lineage as evidenced by reduction in proliferating CD7 + progenitors. We next assessed if CD7 + progenitors derived from cord blood conserved this preferential sensitivity to IL-15.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, in vitro culture of identical progenitors in IL-7 + IL-15 and Notch-ligand resulted in the proliferation of both CD7 + and CD7 − progenitors, arguing against IL-15 purely inducing CD7 on responsive progenitors ( Figure 1 A). Consistent with a recent report [ 17 ], Notch signalling and IL-7 appear to impair commitment towards the NK cell lineage as evidenced by reduction in proliferating CD7 + progenitors. We next assessed if CD7 + progenitors derived from cord blood conserved this preferential sensitivity to IL-15.…”
Section: Resultssupporting
confidence: 92%
“…Notch1 knockdown completely blocks T cell development and increases the accumulation of ectopic B cells in the thymus ( 12 , 13 ). Moreover, Notch1 [and maybe also Notch 2 ( 14 )] regulates the early phases of T cell differentiation in the thymus (through DLL4), but its expression needs to be decreased before T cells can fully differentiate ( 15 ). Upon migration of immature B cells from bone marrow to spleen, an increased level of Notch2 expression regulates the maturation of a subset of B cells that reside in the marginal zone, MZB cells.…”
Section: Notch In Normal Immune Cell Homeostasismentioning
confidence: 99%
“…However, Notch2 does not control other mature B cells including follicular B cells and plasma cells ( 16 ). Moreover, in vitro studies have shown that Notch signaling enhances T- and NK cell differentiation from human hematopoietic progenitor cells (CD34 + ), while inhibiting B cell differentiation ( 14 , 17 ). Notch also has opposing roles in controlling cell fate decisions between two different types of NK cells, i.e., conventional NK cells versus innate lymphoid cell (ILC)-derived natural cytotoxicity receptor (NCR) NKp44 + group (NCR + ILC3)—at different maturational stages of progenitor cells.…”
Section: Notch In Normal Immune Cell Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, high IL-7 and medium Notch signaling favors ILC2 and ILC1/NK cell differentiation, low IL-7 and high Notch signaling favors T cell differentiation in mice (76). The results are however different when human hematopoietic progenitor cells are treated in a similar manner, where IL-7, and Notch signaling induce ILC3 differentiation while suppressing IL-15 induced NK cell differentiation (77). These findings reveal contrasting roles for IL-7 in ILC differentiation which can be explained by differences in mouse and human hematopoiesis and progenitor sources.…”
Section: Il-7rα In the Development Of Ilcs Il-7 And Ilc Developmentmentioning
confidence: 94%